2012
DOI: 10.1039/c2cc33249c
|View full text |Cite
|
Sign up to set email alerts
|

A universal platform for amplified multiplexed DNA detection based on exonuclease III-coded magnetic microparticle probes

Abstract: An amplified multiplexed DNA detection biosensor has been developed, which combines the unique cleavage function of exonuclease III (Exo III) with the separating ability of magnetic microparticles (MMPs). By using different fluorophores, the multiplexed detection of DNA is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Using the cascade signal amplification strategy of the HCR and the enzyme-induced metallization improved the detection sensitivity down to 10 pM, which is about 100-fold lower than that of the conventional unamplified homogeneous assays (Hu et al 2014). The detection sensitivity of this method could be compared to other amplification strategies (Gao and Li 2013; Kong et al 2014; Luo et al 2012; Zhang et al 2013), in which the detection limits were reported commonly in the range of fM to nM. For our method, when the concentration of the T DNA reached down to the 0.1–1 pM range, it was difficult to distinguish the colour change by the naked eyes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the cascade signal amplification strategy of the HCR and the enzyme-induced metallization improved the detection sensitivity down to 10 pM, which is about 100-fold lower than that of the conventional unamplified homogeneous assays (Hu et al 2014). The detection sensitivity of this method could be compared to other amplification strategies (Gao and Li 2013; Kong et al 2014; Luo et al 2012; Zhang et al 2013), in which the detection limits were reported commonly in the range of fM to nM. For our method, when the concentration of the T DNA reached down to the 0.1–1 pM range, it was difficult to distinguish the colour change by the naked eyes.…”
Section: Resultsmentioning
confidence: 97%
“…To meet this challenge, many methods have been well developed, for example, electrochemical sensing (Kong et al 2014; Liu et al 2013a), fluorescence (Hu et al 2013; Niu et al 2010) and chemiluminescence detection (Li and He 2009; Wang et al 2013c), and föster resonance energy resonance energy transfer (FRET) (Liu et al 2013b; Su et al 2014; Xing et al 2013). To further boost the performance, signal amplification strategies with various enzymes are usually adopted, such as exonuclease III-assisted amplification (Gao and Li 2013; Luo et al 2012), rolling circle amplification (Xu et al 2012), and strand displacement amplification (Wang et al 2011; Zhang et al 2013). Among the various signal amplification strategies, the hybridization chain reaction (HCR) attracted particular attention because it doesn’t need any enzymes or labelling processes (Dirks and Pierce 2004; Huang et al 2011; Niu et al 2010; Wang et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…By integrating the sample pretreatment and subsequent detection in the same solution, tubular micro/nanomotor-based biosensors are simple and fast compared to conventional analytical methods [ 103 , 104 , 105 ]. The speed or the fluorescence signal of single tubular micro/nanomotor are generally used as the signal output, thus such biosensors can be utilized to the in-situ detection of the target analytes.…”
Section: Tubular Micro/nanomotors Towards Practical Applicationsmentioning
confidence: 99%
“…In the second case, nanomaterials such as magnetic particles (Luo et al, 2012a;Deng et al, 2013;Persano et al, 2013;Li et al, 2015b), graphene oxide (Lu et al, 2009;Wu et al, 2009;Dong et al, 2010;Li et al, 2010Li et al, , 2014bLi et al, , 2015cWang et al, 2010;Hong et al, 2015;Zhu et al, 2015), nanoparticles (Shi et al, 2013;Luo et al, 2012b;Qiang et al, 2014Qiang et al, , 2015Torabi and Lu, 2014;Wei et al, 2015), are generally applied as quenchers to obtain lower background. Fascinating as developing a zero-background biosensor is, it remains a challenge.…”
Section: Introductionmentioning
confidence: 98%